Penafsiran Hukum tentang “Partisipasi Langsung dalam Permusuhan” dalam Kasus-kasus Kejahatan Perang - Permanasari, Arlina (Jurnal Hukum IUS QUIA IUSTUM, 2019)
Theterm "Direct Participation in Hostilities" is a term contained in the 1949 Geneva Conventions and Additional Protocols of 1977, which gave rise to various legal interpretations. The two international agreements do not provide a definition or further explanation. The problem that arises from this obscurity of interpretation is how judges conduct an analysis of whether someone can be considered as participating in an act of hostility in an armed conflict in war crimes. This research is normative with an analytical descriptive approach towards primary and secondary legal materials obtained from literature studies and analyzed qualitatively based on international humanitarian law. This research aims to identify the interpretation used in the final verdicts of international court on "direct participation in hostilities." The results show that in overcoming the lack of understanding of the term, the ICRC issues an "Interpretive Guidance" that is not legally binding. Although it creates controversy and is not a legal document, the approach adopted in the "interpretive guidance" turns out to have been used as a discussion material making verdicts, but has not been fully used by the judge as a binding legal basis in war crimes.